"China’s One Belt, One Road Policy (OBOR) initiative: Beijing’s interests, OBOR’s features and responses of Regional States with special focus on Malaysia, Pakistan and Bangladesh" - Hossain, Ishtiaq; Rogers, Roy (2020)
For more than seven years now, the One Belt and One Road (OBOR) initiative has been repeatedly used in connection with the analysis of China’s foreign policy under the leadership of President Xi Jinping. It is perfectly legitimate to ask the following questions about OBOR: What is the OBOR Initiative? What are its main features? Why was it launched by China? How did China’s regional Muslim-majority neighbours like Malaysia, Pakistan, and Bangladesh respond to OBOR? This research project was undertaken to deal with those and any other questions that may arise during the course of research. This research project was justified because of the timely nature of the topic and more importantly, it was aimed to fill a gap in the existing literature on the subject matter. While there were plenty of materials on OBOR and its impact on and response to it from perspectives of European, African and Asia countries, very few, if any research had been published focusing on OBOR and response to it from Malaysia, Pakistan and Bangladesh.